Molecular Simulations and Solid-State NMR Investigate Dynamical Structure in Rhodopsin Activation - Mertz, Blake (Biochim Biophys Acta, 2011)
Rhodopsin has served as the primary model for studying G protein-coupled receptors (GPCRs)—the largest group in the human genome, and consequently a primary target for pharmaceutical development. Understanding the functions and activation mechanisms of GPCRs has proven to be extraordinarily difficult, as they are part of a complex signaling cascade and reside within the cell membrane. Although X-ray crystallography has recently solved several GPCR structures that may resemble the activated conformation, the dynamics and mechanism of rhodopsin activation continue to remain elusive. Notably solid-state (2)H NMR spectroscopy provides key information pertinent to how local dynamics of the retinal ligand change during rhodopsin activation. When combined with molecular mechanics simulations of proteolipid membranes, a new paradigm for the rhodopsin activation process emerges. Experiment and simulation both suggest that retinal isomerization initiates the rhodopsin photocascade to yield not a single activated structure, but rather an ensemble of activated conformational states.